2022
DOI: 10.3390/diagnostics12092068
|View full text |Cite
|
Sign up to set email alerts
|

The Urinary Microbiome: Role in Bladder Cancer and Treatment

Abstract: Commensal microbes have increasingly been found to be involved in the development and progression of cancer. The recent discovery of the urinary microbiome bolstered the notion that microbes might play a role in bladder cancer. Although microbial involvement in bladder neoplastic transformation and metastatic progression, except schisto somiasis, has not been established, accumulating research suggests that dysbiosis of the urinary microbiome can produce a chronically inflammatory urothelial microenvironment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 191 publications
0
9
0
Order By: Relevance
“…However, although it is difficult to identify a single group of common bacteria found in a healthy bladder, comparative studies have provided insights into the overlap and various compositions of urine-based microbial communities [33]. One study found that the urinary microbiome is composed primarily of species from a few genera, most frequently Lactobacilli (the generic term 'Lactobacilli' is useful to designate all organisms that were classified as Lactobacillaceae [34]), Gardnerella, and Streptococcus, and has a lower biomass than the vaginal microbiome [31].…”
Section: History Of the Urinary Microbiome Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although it is difficult to identify a single group of common bacteria found in a healthy bladder, comparative studies have provided insights into the overlap and various compositions of urine-based microbial communities [33]. One study found that the urinary microbiome is composed primarily of species from a few genera, most frequently Lactobacilli (the generic term 'Lactobacilli' is useful to designate all organisms that were classified as Lactobacillaceae [34]), Gardnerella, and Streptococcus, and has a lower biomass than the vaginal microbiome [31].…”
Section: History Of the Urinary Microbiome Studiesmentioning
confidence: 99%
“…Due to the significant anatomical and physiological differences between men's and women's lower urinary tracts, it is not surprising that the urine microbiome of the bladder also exhibits unequal stratification [33]. One study discovered that Firmicutes, Actinobacteria, Bacteroidetes, and Proteobacteria were the phyla that men and women shared most frequently.…”
Section: History Of the Urinary Microbiome Studiesmentioning
confidence: 99%
“…Studies have shown that urinary microbes play an important role in the development of urolithiasi, interstitial cystitis, bladder cancer and attention de cit hyperactivity disorder (ADHD) [22,23,[50][51][52] . However, the role of urethral microbes in the development of PNS has rarely been reported.…”
Section: Disscussionmentioning
confidence: 99%
“…(2) Bladder cancer: Some studies have demonstrated that the UM is associated with bladder cancer transformation and metastatic progression. It has further been suggested that dysbiosis of the UM produces a chronically inflammatory urothelial microenvironment which leads to bladder cancer [45]. However, it remains unknown whether the UM affects the development or progression of bladder cancer, or whether bladder cancer is responsible for the alternation of the UM [6].…”
Section: ) Urological Cancers and Ummentioning
confidence: 99%